A REVIEW ON PHYSIOLOGY OF MANASA (PSYCHE) IN AYURVEDA - Gupta, *Ankita; Jalan, Shaily; Chander, Bipan (International Journal of Ayurveda and Pharma Research, 2018)
Mental health is given equal importance at various places in Ayurvedic texts. Ayurveda emphasizes that Sharira (body) and Sattva (mind) both interact with one another in all spheres of life. The Ayurvedic approach towards health and disease is entirely psychosomatic in its nature. Ayurveda greatly emphasizes on the phenomena of mind than that of the body. This can be expounded by the definition of health, the causes of disease, the approach to the examination of the patient, the concept of the psychosomatic constitution i.e. Prakruti, the regimen of mental and physical hygiene. Therefore it is imperative to understand about the physiology, functions and enactments of Mind i.e. Manasa in Ayurveda. This review article is based upon the fundamentals describing Manasa and its functions and physiology. It is very important to understand each and every aspect of Manas for an Ayurvedic scholar or physician for complete knowledge of human body and behavior.